Isolation, biological activity and biochemical characterization of lectin from chenopodium quinoa willd seeds. (cv. Salcedo-INIA) - Huarachi-Valencia, Juan-Pablo; Gonzales-Alcos, Vicky-Cristina; Cervantes-Alagon, Sheyla; Cusi-Zamata, Luz-Wilfreda (2022)
Lectins act as cell recognition molecules, and probably in plant defense. The CqLEC, lectin from Ch. quinoa cv Salcedo INIA, was isolated, purified and characterized from 70 g of seeds through saline extraction, and the combination of two molecular exclusion chromatographies such as Sephadex G-100 and G -75, obtaining 5.53 mg/ml of protein with hemagglutinating activity, as well as by reverse phase HPLC at 32 minutes with 54% buffer B, indicating that it had a low number of hydrophobic residues in its structure. Likewise, SDS-PAGE showed that the purified lectin was homogeneous since it had a single component corresponding to a 12.82 kDa protein. Being that the CqLEC agglutinated human erythrocytes of the “O Rh+” blood group with an MHC of 1.95 μg/ml, inhibited by fucose (0.78 mM) and the chelating agent EGTA (0.1 mM), this indicated that would be a fucose-binding lectin dependent on divalent ions such as calcium or manganese. On the other hand, this protein showed specific bactoagglutination for E. coli (CMB equal to 200 μg/ml), as well as insecticidal activity against Symmetrischema plaesiosema larvae (1000 ppm of CqLEC, P < 0.05). Complete amino acid analysis revealed that CqLEC is an acidic lectin (70.54% hydrophilic residues and 29.46% hydrophobic residues), with glutamic acid (33%) prevailing, with a molecular mass of 12.859 kDa. By sequential homology study, it was determined that it belongs to the family of vegetable lectins of Legumes, showing 82.1% similarity with the precursor of agglutinin I extracted from the bark of Cladrastis kentukea. The CqLEC also presented highly conserved residues in its structure, such as Leu 4, Ser 6 and Phe 7.
Keywords: lectin; Chenopodium quinoa; bactoagglutination; insecticidal activity